Impact of Artificial Intelligence on Perceived Satisfaction in Living Smart Cities as mediated by Subjective Well-being and Trust - Anayat, Barezah (American Journal of Business Science Philosophy, 2025)
This study investigates the impact of artificial intelligence (AI) on trust, subjective well-being, and perceived satisfaction in smart cities. A cross-sectional survey was conducted with urban residents in Pakistan, using a 5-point Likert scale to gather responses. The study hypothesized that AI influences trust, well-being, and satisfaction, and that trust and subjective well-being mediate these relationships. Structural Equation Modeling using SmartPLS software was applied for data analysis. The results indicate that AI has a significant positive effect on trust, subjective well-being, and perceived satisfaction. Trust and well-being were found to mediate the relationship between AI and satisfaction, highlighting their critical roles in enhancing residents’ experiences in smart cities. The findings emphasize the importance of designing AI systems that foster trust and improve well-being to maximize satisfaction among smart city residents. Theoretical contributions include the application of trust and subjective well-being frameworks in the context of AI and smart cities. Practically, the study offers insights for policymakers and urban planners to develop user-friendly, transparent, and reliable AI systems.